MEMBANGUN TUNAS INTEGRITAS SEBAGAI CIKAL GENERASI ANTIKORUPSI DI TINGKAT PENDIDIKAN DASAR - SUHARDIANA, I PUTU ANDRE (Institut Hindu Dharma Negeri Denpasar, 2017)
A series of efforts in order to minimize corruption in Indonesia has been conducted on an ongoing basis. The formation of Indonesia’s Corruption Eradication Commission (KPK) is one of the real actions of preventing corruption in a holistic manner, both preventively and curatively. Considering the vast territory of Indonesia and the large population, the emergence consistency of corruption cases is an indicator of the powerless of Indonesia’s Corruption Eradication Commission (KPK) to stem this problem independently. This Commission needs support. Families, schools, and societies as frontlines in forming high quality individuals who are not having legal defect in the acts of corruption, are tremendous assets and weapon whose role needs to be maximized in various lines of combating corruption. Schools, for example, this place is the first capital in forming anti-corruption generation through the implementation of flagship programs related to the outage of corruption guerrilla which increasingly rampant recently. Specifically, the primary school is the most important force, because in this place, the children transitional period between the early age to teenager are getting the forging of character formation that covers all aspects, not only the improvement of cognitive side. Planting positive personality through a series of anti-corruption activities should be integrated in various subjects that are packaged in such a way that is interesting to be accepted by students. This is an activity that can no longer be delayed for its implementation. Moreover, the students are given the opportunity to develop their knowledge and logical reasoning on the various dimensions of anti-corruption, because the essential characteristics of anti-corruption education are the synergy between the use of information and knowledge with the ability to make moral judgments. If all parties are actively involved in its application, then it will be an investment program of long-term corruption prevention actions. Surely this is the dream of all citizens in order to create good governance which would impact on the welfare of the people as much as possible.